2022
DOI: 10.37391/ijeer.100236
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm to Secure Data in New Generation Health Care System from Cyber Attacks Using IoT

Abstract: The rise of digital technology has essentially enhanced the overall communication and data management system, facilitating essential medical care services. Considering this aspect, the healthcare system successfully managed patient requirements through online services and facilitated patient experience. However, the lack of adequate data security and increased digital activities during Covid-19 made the healthcare system a soft target for hackers to gain unauthorized access and steal crucial and sensitive info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In [16], During COVID-19, data security issues became increasingly pressing for the healthcare sector. Since the virus's spread in early 2020, it has been joined by an increasing number of malicious hackers hunting for deficiencies in the healthcare system's data maintenance network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [16], During COVID-19, data security issues became increasingly pressing for the healthcare sector. Since the virus's spread in early 2020, it has been joined by an increasing number of malicious hackers hunting for deficiencies in the healthcare system's data maintenance network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quantum computing research has come a long way recently, and both school and business are putting a lot of money into making quantum computers that can be used in real life. Quantum hardware systems, such as superconducting qubits, trapped ions, and topological qubits, show different ways to reach the elusive goal of quantum computing that can be scaled up and can still work even when something goes wrong [15].Companies like IBM, Google, and Rigetti Computing, which are big names in the field, have made important steps forward in building quantum computers with higher qubit numbers. Google's claim of quantum supremacy with its Sycamore processor was a turning point because it showed that a certain job could be done faster than the most powerful traditional supercomputers.But the field has to deal with major problems.…”
Section: B Current State Of Quantum Computing Researchmentioning
confidence: 99%
“…The IIoT has the potential to boost efficiency, production, and operational efficiency in a variety of sectors. The existing services are initially improved by IIoT with the ultimate goal of creating entirely intelligent and enhanced services and products [6][7][8][9][10]. This has enabled most of the organization to grab knowledge about how and where IIoT innovations and solutions have to lead to transformations in the organization, enhanced goods, and services quality.…”
Section: ░ 1 Introductionmentioning
confidence: 99%
“…The potential of IDS to track and foresee hostile conduct and unknown attacks has sparked a surge of interest in anomaly detection research. Current machine learning-based irregularity detection algorithms, on the other hand, have a significant false alarm rate [10]. Therefore, deep learning models can be utilized for efficient attack detection.…”
Section: ░ 1 Introductionmentioning
confidence: 99%